The Association of Delayed Milk Ejection and Milk Production in Dairy Cows Milked by an Automated Milking System - Matthias Wieland; Heleen ten Have (Animals)
This retrospective cohort study examined the association between delayed milk ejection (DME), defined as bimodal milk flow, and milk yield in dairy cows milked with an automated milking system (AMS). Additionally, we identified risk factors for DME. Using data from a farm milking approximately 1350 cows, we analyzed 689,484 individual milking records and 194,142 daily cow observations over 350 days with generalized linear mixed models. Cows with DME generally had higher daily milk yields, regardless of lactation number. However, first-lactation cows early in lactation and older cows (≥third lactation) late in lactation produced less milk when experiencing DME. In contrast to the higher daily milk yield, cows produced less milk per milking when experiencing delayed milk ejection. However, more frequent milkings contributed to higher daily milk yield, even with more instances of delayed milk ejection. Risk factors for DME included lactation number, stage of lactation, milking frequency, and milking interval. These findings underscore the complexity of DME in AMS and suggest that optimizing individualized milking protocols could improve milk yield efficiency. Understanding the interplay of cow characteristics and milking management may enhance AMS performance and dairy herd productivity.